Critical Study of the Issuance of Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 of 2014 concerning Villages in Indonesia - Robert Libra; Sudi Fahmi; Silm Oktapani (International Conference On Law And Social Sciences, 2024)
The village government is at the forefront of efforts to realize the welfare and prosperity of the population. Villages have a legal basis in Law no. 6 of 2014 concerning Villages which was amended in Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 of 2014 concerning Villages. In the amended law there are several things that could erode the rights of village residents and future legal developments, such as the term of office of the village head, the use of village funds, and the election of a single candidate for village head. The formulation of the problem raised is how a critical study of Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 of 2014 concerning Villages in Indonesia is the answer to village problems. The research method used is normative juridical with a statutory approach and a conceptual approach. The results of this research show that the term of office of village heads was extended from 6 years to 8 years in the latest amended law, which has the potential to create a loophole for conducting corruption, collusion and nepotism. Apart from that, the existence of a village fund entity for villages mentioned in Article 5A paragraph (1) of the amendment law requires that there be opportunities for misuse. Then it concerns the election of a single village head which is entirely carried out by the Village Consultative Body which erodes the essence of democracy and people's sovereignty at the village level. Several things that can be done are changing the concept of electing a single village head by continuing to carry out village head elections to maintain the sovereignty of the people in the village. Apart from that, the use of village funds should also be tightened in terms of their use so that it can be a progress for future village development.